2016
DOI: 10.1242/jeb.135509
|View full text |Cite
|
Sign up to set email alerts
|

Be ready at any time: postprandial synthesis of salivary proteins in salivary gland cells of the haematophagous leech Hirudo verbana

Abstract: Sanguivorous leeches are ectoparasites having access to body fluids of potential hosts only infrequently. During feeding, salivary proteins are released from unicellular salivary glands into the wound. These substances, among them anti-coagulants, anti-inflammatory or antimicrobial agents, allow these animals proper feeding and long-term storage of host blood in their crops for several months. Using histological, protein biochemical and molecular techniques, we investigated whether synthesis of salivary protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Most of these studies used leeches that had been starved for a certain period of time (Scacheri et al, 1993). Lemke, Müller & Hildebrandt (2016) reported that feeding-associated salivary protein content was reduced when Hirudo verbena started feeding until the fifth day after feeding. For the hirudin-HN in our study, the protein content of FG was lower than that of the other two groups (UFG and FIG), which was consistent with the trend in Lemke, Müller & Hildebrandt’s (2016) research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies used leeches that had been starved for a certain period of time (Scacheri et al, 1993). Lemke, Müller & Hildebrandt (2016) reported that feeding-associated salivary protein content was reduced when Hirudo verbena started feeding until the fifth day after feeding. For the hirudin-HN in our study, the protein content of FG was lower than that of the other two groups (UFG and FIG), which was consistent with the trend in Lemke, Müller & Hildebrandt’s (2016) research.…”
Section: Discussionmentioning
confidence: 99%
“…Lemke, Müller & Hildebrandt (2016) reported that feeding-associated salivary protein content was reduced when Hirudo verbena started feeding until the fifth day after feeding. For the hirudin-HN in our study, the protein content of FG was lower than that of the other two groups (UFG and FIG), which was consistent with the trend in Lemke, Müller & Hildebrandt’s (2016) research. In addition, similar to the activity in the blood-sucking leech P. manillensis , the anticoagulant activity was higher in the head than in other parts of the body (Gou et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…During one act of blood meal, medicinal leeches partially or completely empty their salivary gland cells [11]. Salivary gland cells have been shown to replenish their reservoirs with the content of SCS within 7 days after blood meal [12]. In addition to its known inhibitory effect on haemostasis and blood coagulation, SCS suppresses inflammation, exhibits analgesic effects, possesses antimicrobial activity, and alters vasodilatory responses, enhancing local blood circulation to facilitate leech feeding.…”
Section: Introductionmentioning
confidence: 99%
“…Some leech-specific anticoagulants were also found in leeches that do not feed on blood, such as Whitmania pigra [62]. Interestingly, these anticoagulants were upregulated after feeding [62] just as they are in blood-feeding leeches [63].…”
Section: Salivary Proteins: Natural Drugs From Medicinal Leechesmentioning
confidence: 98%